Modeling Workflow Processes Based on Tasks and Transactions: A Case Study of the UPM Graduate School Office - Cheang, Mei Chuin (1997)
Workflow binds, integrates the people, the processes, and the organisation into a value chain. Workflow modeling is used to redesign work processes to increase the efficiency and productivity of work. Workflow is said to be the technological cousin to Business Process Reengineering. Workflow carries the promise of integrating office work, resulting in short delay times, improved customer services and better knowledge of logistics parameters of office work. Workflow systems support business systems by maintaining the logical sequence of transitions between tasks in a work process, making sure that all related tasks or a process are completed. Tasks and transactions form an integral part of a workflow management system. However, workflow modeling is a relatively new field. Many organisations intending to conduct business process re-engineering are finding it difficult to obtain frameworks to model their workflows. This study presents the development of a framework for these organisations to model workflow processes. Old workflow processes are studied from a selected organisation and a new workflow model is designed. The performance improvements of the new workflow model over the old workflow model are then quantified. From here, a framework for workflow modeling is produced for future reference. Important concepts and issues that need attention when modeling workflows, are discussed. These issues can be used to overcome setbacks faced by many organisations while modeling their workflows, such as identifying problems in the workflow and redesigning a workflow model that will increase productivity. From this study, it is revealed that redesigning workflows require that each process be looked into carefully for its flaws and problems, to look for measures to improve the processes, and to redesign these workflow processes with attention given to issues,such as allowing the workflow model to be open, reusable, portable and scalable. With these issues in reference, workflow modeling can then be successfully implemented, for the re-engineering of any organisation.